Changes in Myosin from Silver Carp (Hypophthalmichthys molitrix) under Microwave-Assisted Water Bath Heating on a Multiscale - Haihua Cong; He Lyu; Wenwen Liang; Ziwei Zhang; Xiaodong Chen (Foods, 2022)
To further prove the advantages of microwave-assisted water bath heating (MWH) in low-value fish processing, the effects of different heating methods (two heating stage method, high temperature section respectively using MWH1, MWH2, MWH3, WH—water heating, MH—microwave heating) on secondary and tertiary myosin structures, SDS-PAGE, surface morphology, scanning electron microscopy (SEM), and particle size distribution were compared and analyzed. The findings revealed that MH and MWH aided in the production of gel formations by promoting myosin aggregation. Myosin from silver carps demonstrated enhanced sulfhydryl group and surface hydrophobicity after MWH treatment, as well as a dense network structure. The distribution of micropores becomes more uniform when the microwave time is increased. Actually, the total effect of microwave time on myosin is not substantially different. The correlation between particle size distribution and protein aggregation was also studied, in terms of time savings, the MWH of short microwave action is preferable since it not only promotes myosin aggregation but also avoids the drawbacks of a rapid warming rate. These discoveries give a theoretical foundation for understanding silver carp myosin under microwave modification, which is critical in the food industry.